2016
DOI: 10.1038/srep33877
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza A(H7N9) and (H5N1) infections among poultry and swine workers and the general population in Beijing, China, 2013–2015

Abstract: Although several studies have reported seroprevalences of antibody against avian influenza A(H7N9) virus among poultry workers in southern China, results have varied and data in northern China are scarce. To understand risks of H7N9 and H5N1 virus infections in northern China, a serological cohort study was conducted. Poultry workers, swine workers and the general population in Beijing, China, were evaluated through three surveys in November 2013, April 2014 and April 2015. The highest seroprevalence to H7N9 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although most of those exposures may correspond to LPM visits, other opportunities for contact with poultry along the production and value chain also exist. For example, poultry workers in Beijing were shown to be at a higher risk for H7N9 infection than the remaining population of the city ( 24 ). Poultry may become a reservoir when the circulation of avian influenza viruses through the production and value chains cannot be prevented; poultry-related variables were found to be key predictors of H7N9 risk in several previously published studies ( 20 , 23 , 25 , 26 ).…”
mentioning
confidence: 99%
“…Although most of those exposures may correspond to LPM visits, other opportunities for contact with poultry along the production and value chain also exist. For example, poultry workers in Beijing were shown to be at a higher risk for H7N9 infection than the remaining population of the city ( 24 ). Poultry may become a reservoir when the circulation of avian influenza viruses through the production and value chains cannot be prevented; poultry-related variables were found to be key predictors of H7N9 risk in several previously published studies ( 20 , 23 , 25 , 26 ).…”
mentioning
confidence: 99%
“…In that study, the absence of confirmed infections or severe illnesses in poultry workers with serological evidence of recent infection is also consistent with most infections being mild. A study in Beijing estimated very low risks of H7N9 in poultry workers in Beijing, and did not identify any infections in 1300 person-years of exposure among the general population from 2013 to 2015 [15]. …”
Section: Discussionmentioning
confidence: 99%
“…The incidence density rate for H9N2 viral infections (from 2013 to 2015, 3.08 per 1000 person‐months) among all the study participants was found to be higher than those for H7N9 (0.4 per 1000 person‐months) and H5N1 (1.3 per 1000 person‐months) infections observed in the same period with the same population (HI assay; HI cutoff titer, 80). Another study conducted in Guangdong Province, China, also revealed that the seroprevalence of anti‐H9N2 antibodies (6.79%) was higher than for H7N9 (3.95%), H5N1 (1.36%), and even avian‐like canine H3N2 (1.85%) (HI assay; HI cutoff titer, 40).…”
Section: Discussionmentioning
confidence: 66%